Pravorečna problematika s splošnoslovaropisnega vidika - Mirtič, Tanja (Slavia Centralis, 2020)
Orthoepic problems from the standpoint of general lexicography The aim of this article is to present, in their main outlines, orthoepic data in the general explanatory dictionary and, at the same time, on the basis of survey analysis, to establish the need for an orthoepic manual amongst those employed in the media sector, theatres and film production industry, as well as to shed light on the most important problem areas of Slovenian orthoepy from the respondents’ point of view. In the last part, the article addresses the deficiency of basic research in the field of spoken Standard Slovene and the great importance of regular monitoring and collecting of orthoepic problems detected by general language users and experts, professionally dealing with spoken Standard Slovene. Another emphasis is also on the need for a well thought out corpus that would allow reliable orthoepic analyses